AN ACTIVE TRIPLE SYSTEM 44i BOOTIS - Pribulla, T.; Tremko, J.; Rovithis-Livaniou, H.; Rovithis, P. (Одеські астрономічні публікації, 2017)
The long-term UBV R photoelectric monitoring of 44i Boo performed at the Skalnate Pleso, Stara Lesna and Kryonerion observatories is presented. The orbital period changes are discussed including light-time effect caused by the visual companion. The radial velocity of the visual companion as well as observed period change conclusively determine the ascending node of the visual orbit to be in the first quadrant. The light curve of the system was found to be quite stable but asymmetric: maximum in the phase 0.25 has always been fainter than maximum in the phase 0.75. Light-curve analysis of the V observations since 1998 provided new inclination angle i=73.66 ± 0.14°. Combination of the inclination angle with the published spectroscopic elements gave reliable masses of the components: m 1 =0.861±0.008 M ⊙ and m 2 = 0.419±0.11 M ⊙.